Analog circuit design immersion in the black art of analog design - Dobkin, Bob; Williams, Jim (Elsevier, 2013)
With the growth of digital systems, wireless communications, complex industrial and automotive systems, designers are being challenged to develop sophisticated analog solutions. This source book of circuit design solutions aids engineers with elegant and practical design techniques that focus on common analog challenges.